2013
DOI: 10.1186/1478-811x-11-31
|View full text |Cite|
|
Sign up to set email alerts
|

The role of LPA and YAP signaling in long-term migration of human ovarian cancer cells

Abstract: BackgroundThe Hippo-YAP signaling pathway is altered and implicated as oncogenic in many human cancers. However, extracellular signals that regulate the mammalian Hippo pathway have remained elusive until very recently when it was shown that the Hippo pathway is regulated by G-protein-coupled receptor (GPCR) ligands including lysophosphatidic acid (LPA) and sphingosine 1-phosphophate (S1P). LPA inhibits Lats kinase activity in HEK293 cells, but the potential involvement of a protein phosphatase was not investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
127
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 52 publications
(84 reference statements)
5
127
0
Order By: Relevance
“…Such promigratory effect could be attributed in part to the increase of YAP transcriptional activity in RASSF1A-depleted cells. YAP promigratory effects have been already reported in ovarian cancer cells treated by LPA (34) or in Drosophila border cells migration (35). In line with such data, we report here that RASSF1A knockdown promotes a nuclear accumulation of active YAP.…”
Section: Discussionsupporting
confidence: 79%
“…Such promigratory effect could be attributed in part to the increase of YAP transcriptional activity in RASSF1A-depleted cells. YAP promigratory effects have been already reported in ovarian cancer cells treated by LPA (34) or in Drosophila border cells migration (35). In line with such data, we report here that RASSF1A knockdown promotes a nuclear accumulation of active YAP.…”
Section: Discussionsupporting
confidence: 79%
“…Here the levels of Amot130, but not AmotL1, are shown to directly respond to serum starvation through phosphorylation by LATS, which in turn is a critical event for Hippo-induced growth arrest. Future experiments examining other inhibitors of YAP, such as PP1 (38), glucagon, and epinephrine (2), for their effects on Amot130 phosphorylation may further establish how this event is central to Hippo signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that PP1A acts downstream of RhoA in LPA-induced YAP dephosphoryaltion (25) and PI3K and ERK1/2 signaling is involved in the regulation of PP1A activity in cancer cells (26,27). Conceivably, netrin-1 elevates YAP stability through regulating PP1A activity induced by the signaling transduced from the binding of netrin and its receptors.…”
Section: Discussionmentioning
confidence: 99%